MXene Electrode Materials for Electrochemical Energy Storage: First-Principles and Grand Canonical Monte Carlo Simulations. (2019) - Okada, Yasuaki; Keilbart, Nathan; Goff, James M.; Higai, Shin'ichi; Shiratsuyu, Kosuke; Dabo, Ismaila
Abstract : MXenes are a novel class of two dimensional materials, discovered by Barsoum and Gogotsi [M. Naguib, J. Come, B. Dyatkin, V. Presser, P. Taberna, P. Simon, M. W. Barsoum, and Y. Gogotsi, Electrochemistry Communications 16, 61-64 (2012); B. Anasori, M. R. Lukatskaya, and Y. Gogotsi, Nature Reviews Materials vol. 2, 16098 (2017)]. Their large specific surface area and the tunability of their physicochemical properties as a function of the transition metal and surface terminal group make them a unique design platform for various applications, a primary example of which is pseudocapacitive energy storage. However, there is still incomplete understanding of how the transition metal chemistry and stoichiometry, and the surface termination affect charge storage mechanisms in MXene. In this study, we have performed systematic first-principles calculations for bulk MXene and found that the atomic charge of the metal cations, which is related to their valence, decreases across the d-electron metal series. Electronic-structure indicators of performance are examined to understand the energy storage behavior, whereby charges are stored between the terminal groups and adsorbing cations. Importantly, we found that the differential Bader charges show good agreement with theoretical capacitances and are useful in predicting charge storage trends in MXene-based pseudocapacitors. Furthermore, we have performed first-principles and grand canonical Monte Carlo calculations for the slab systems, finding that the solvent plays a critical role in enhancing the pseudocapacitive response.